2013
DOI: 10.3390/ijms14034982
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Ceramide as Collaborators in the Stress Response

Abstract: The sphingolipid ceramide mediates various cellular processes in response to several extracellular stimuli. Some genotoxic stresses are able to induce p53-dependent ceramide accumulation leading to cell death. However, in other cases, in the absence of the tumor suppressor protein p53, apoptosis proceeds partly due to the activity of this “tumor suppressor lipid”, ceramide. In the current review, we describe ceramide and its roles in signaling pathways such as cell cycle arrest, hypoxia, hyperoxia, cell death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 195 publications
(219 reference statements)
2
23
0
Order By: Relevance
“…It will be interesting to investigate potential crosstalk between the Cn mediated retrograde signaling reported by us and other reported retrograde signaling pathways such as ROS-induced TFGβ signaling, HIF1α, Ras, p53 signaling (Jain, Rivera et al 2013;Hage-Sleiman, Esmerian et al 2013). Identifying a convergence point of these various signaling modes will help in elucidating the global picture of mitochondrial retrograde signaling.…”
Section: Future Perspectivesmentioning
confidence: 83%
“…It will be interesting to investigate potential crosstalk between the Cn mediated retrograde signaling reported by us and other reported retrograde signaling pathways such as ROS-induced TFGβ signaling, HIF1α, Ras, p53 signaling (Jain, Rivera et al 2013;Hage-Sleiman, Esmerian et al 2013). Identifying a convergence point of these various signaling modes will help in elucidating the global picture of mitochondrial retrograde signaling.…”
Section: Future Perspectivesmentioning
confidence: 83%
“…It has been shown by our group [4,25,43,51] and others [52][53][54] that ceramides, in increased levels, found in the atherogenic process[mixed in plaques; unpublished findings ], at least in rabbits, and stimulated in MgD states could be important causal and initiating agents [16,17].…”
Section: Causative Events and Pathways Leading To Inflammationatherogmentioning
confidence: 99%
“…We have recently demonstrated that cerebral, aortic and coronary VSM cells can also elaborate and release PAF [69]. There are some reports that both PAF and ceramides may result in transformation of VSM cells from one phenotype to another, as is typical in the atherosclerotic process [53,54,72,73]. In addition, like we see in MgD, PAF produces vasoconstriction of blood vessels and a variety of VSM types [for recent review, see 69], as do several of the ceramides [69,74,75].…”
Section: Is the Mysterious Intermediary Molecule Possibly Related To mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of ceramidases were reported to induce apoptosis and cause cell cycle arrest (Bhabak et al 2013). Therefore, pharmaceutical/preclinical research and later clinical trials of cancer cases may include ceramide and sphingolipids (Sleiman et al 2013) as well ceramidases. In the treatments with ceramidase inhibitors or exogenous ceramides cell cycle arrest and apoptosis are induced by increasing the ceramide concentration in the cells of breast (Sanger et al 2015) and prostate cancers (Beckham et al 2012).…”
Section: Introductionmentioning
confidence: 99%